Efektivitas Penggunaan Media Big Book terhadap Keterampilan Membaca Nyaring Siswa Sekolah Dasar - Kartini, Kartini; Al Wahid, Sucahyo Mas’an; Wulandari, Sartika Tri (Lembaga Yasin AlSys, 2025)
Big book media is a media that has unique characteristics in terms of size, text, color and images to make it easier for students to understand reading. This research aims to determine the effectiveness of using Big Book media on students' reading aloud skills in elementary schools. This type of research is pre-experimental research involving one class as an experimental class without a control class with the One Group Pretest-posttest research design. The results of this research indicate that the Big Book media is quite effective for reading aloud skills for low class students as indicated by the mean value of the n gain score being 0.6335, which is in between so that the n gain score category is medium, which means that the effectiveness is medium as well if seen from the mean value. in ngain_persen, namely 63.35%, you can see the estimated effectiveness of the ngain score in percentage, namely the estimate is quite effective. So that the use of Big Book media is effective for elementary school students' reading aloud skills.